2020
DOI: 10.3390/molecules25194503
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Electrical and Electrochemical Properties of Magnesium Ion Conducting CS: PVA Based Polymer Blend Electrolytes: Role of Lattice Energy of Magnesium Salts on EDLC Performance

Abstract: Plasticized magnesium ion conducting polymer blend electrolytes based on chitosan (CS): polyvinyl alcohol (PVA) was synthesized with a casting technique. The source of ions is magnesium triflate Mg(CF3SO3)2, and glycerol was used as a plasticizer. The electrical and electrochemical characteristics were examined. The outcome from X-ray diffraction (XRD) examination illustrates that the electrolyte with highest conductivity exhibits the minimum degree of crystallinity. The study of the dielectric relaxation has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 94 publications
0
22
0
Order By: Relevance
“…The leaf-like shape of the CV curve is observed at a higher scan rate turned to a rectangular-like shape when the scan rates are reduced. The factors that affect these changes could be the porosity of carbon electrodes and the internal resistance presence during the scanning process [ 101 , 102 ]. The non-Faradaic process means the EDLC’s charge storage mechanism depends on ion buildup at the interfaces between electrodes and electrolytes [ 48 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The leaf-like shape of the CV curve is observed at a higher scan rate turned to a rectangular-like shape when the scan rates are reduced. The factors that affect these changes could be the porosity of carbon electrodes and the internal resistance presence during the scanning process [ 101 , 102 ]. The non-Faradaic process means the EDLC’s charge storage mechanism depends on ion buildup at the interfaces between electrodes and electrolytes [ 48 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study has shown that dielectric properties of the PE are highest with incorporation of 50 wt.% of glycerol. This indicates the existence of a large number of charge carrier and thus relatively high conductivity [77].…”
Section: Dielectric Propertiesmentioning
confidence: 97%
“…Aniskari et al [68] also reported the highest conducting electrolyte also had the highest percentage of free ions. By employing the percentage of free ions for each electrolyte, the transport parameters of number density (n), ionic mobility (µ), and diffusion coefficient (D), can be calculated using the Equations (16)- (18), where N A is Avogadro's constant, M represents the number of moles of glycerol, and e is the elementary charge. V Total is the total volume of the polymer electrolytes.…”
Section: Ftir Resultsmentioning
confidence: 99%
“…It has been reported that EDLC has higher power density and easier fabrication methods compared to Faradaic capacitor or pseudocapacitor [ 15 , 16 , 17 ]. Activated carbon is the most commonly used active material in the electrodes of an EDLC [ 18 , 19 , 20 ]. Various activated carbons have been synthesized from different sources such as nori-based [ 21 ], tofu-based [ 22 ], dimocarpus longan-based [ 23 ], coconut shell-based [ 24 ], and many more.…”
Section: Introductionmentioning
confidence: 99%